Gambaran Pengetahuan Tentang Pemeriksaan Payudara Sendiri (Sadari) Pada Wanita Usia Subur (WUS) - Yuwansyah, Yeti; Suyanti, Suyanti; Cantika, Triana (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Introduction. Breast cancer can be detected early by means of Breast Self-Examination (BSE) to find out the early stages. BSE knowledge in women of childbearing age (WUS), namely women who enter the age of 15-49 years is very important. The purpose of this study was to describe the knowledge of BSE in WUS at BPM Midwife Erni Ramayanti, Amd.Keb. Research methods. This research uses quantitative descriptive research. The population of this research is all WUS in BPM Erni Ramayanti Mekarmulya Village as many as 185 people and the sample is 63 people with purposive sampling technique. This research was conducted in June-July 2022. Univariate data analysis used frequency distribution. Research results and conclusions. The results showed that less than half (27.0%) WUS had less knowledge about BSE. A small part (11.1%) have less knowledge based on understanding, less than half (36.5%) have less knowledge based on goals, less than half (42.9%) knowledge based on the benefits of BSE is lacking, a small part (22.2%) less knowledgeable based on impact and more than half (60.3%) lack knowledge based on implementation. Midwives or health workers need to increase counseling or counseling activities to WUS regarding BSE with methods that are easy to understand and understand, such as using leaflets, booklets or demonstration methods. WUS are expected to actively access information about BSE, both from the media and from health workers.